A Single‐Phase, All‐Solid‐State Sodium Battery Using Na3−xV2−xZrx(PO4)3 as the Cathode, Anode, and Electrolyte. Issue 5 (23rd December 2016) - Inoishi, Atsushi; Omuta, Takuya; Kobayashi, Eiji; Kitajou, Ayuko; Okada, Shigeto
Abstract : "Single‐phase" all‐solid‐state battery, based on Na3− x V2− x Zr x (PO4 )3 as the cathode, anode, and electrolyte, is reported. It successfully undergoes room temperature charge–discharge reactions based on the V 3+ /V 2+ (anode) and V 3+ /V 4+ (cathode) redox systems with insertion reaction. The interfacial resistance is essentially zero at the anode and cathode.